Estudo de avanço e atraso de luz em chip integrado utilizando moléculas fotônicas - Fujiwara, Pedro Luís Yendo (Universidade Federal de São Carlos, 2025)
Integrated photonics enables miniaturization and efficiency in the optical processing of information on chips. To enhance the fast and slow light effects without increasing the area occupied by the components, this work proposes the use of photonic molecules (PMs), composed of microcavities in the form of rings internally coupled to an outer ring. We investigate a PM with an outer ring of 20 μm and an inner ring of 5 μm, fabricated on silicon-on-insulator (SOI), analyzing its spectrum and its impact on the light advance and delay times. Numerical simulations based on data extracted from a fabricated PM demonstrate that the proposed structure can achieve group delays of up to 120 ps (slow light) and advances on the order of 70 ps (fast light), values compatible with applications such as optical buffers, phase modulation, and dispersion compensation. Comparisons with larger devices reported in the literature reinforce that PMs offer excellent spectral efficiency and significant area reduction, optimizing the performance of integrated photonic circuits. Additionally, after studying the coupling coefficients t₁ and t₂, it was possible to optimize these effects further, reaching delays of up to 143.60 ps and advances of up to 100.19 ps.
Study of fast and slow light on an integrated chip using photonic molecules
Keywords: Fotônica integrada; Moléculas fotônicas; Luz lenta e rápida; Guias de onda; Silício-sobre-isolante; ENGENHARIAS::ENGENHARIA ELETRICA::TELECOMUNICACOES